THE LEGAL STATUS OF PARTIES IN CONSTITUTIONAL COMPLAINT PROCEEDINGS BEFORE THE CONSTITUTIONAL COURT - Noila Doniyorovna Nurmamatova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines the legal status of parties in the proceedings of the Constitutional Court based on constitutional complaints, their forms of participation, and comparative analysis with legal models in foreign practice. The author analyzes who the parties are, their powers, availability of procedural instruments, and mechanisms for participation through lawyers, representatives, and written submissions. The experience of countries such as Germany, France, the USA, Spain, and the United Kingdom is also analyzed. The article critically evaluates the situation in Uzbekistan and offers proposals to expand the right to direct access to the court and to diversify participation forms.